IMPLEMENTASI PENJAMINAN MUTU INTERNAL SEKOLAH : Studi Kasus di SMA Pesantren Unggul Al Bayan Kabupaten Sukabumi - Dian Sudiana Raflan, - (2019)
The implementation of school internal quality assurance in a mechanism for fulfilling quality that runs in educational units and is carried out by all components in an education unit continuously. Continuous quality improvement is a quality management approach that focuses on the process and improvement. The purpose of this study was to obtain an overview of the implementation of the school's internal quality assurance and the implementation of continuous quality improvement (CQI) at the Al Bayan Excellent Islamic Boarding High School in Sukabumi Regency. This thesis is a qualitative study with a case study approach through interviews, observation, and documentation studies. The results of this study indicate that the Al Bayan Excellent Islamic Boarding High School is a school with a category of educational units that implements good school internal quality assurance and continuous quality improvement (CQI).